Plasma-Derived Exosome MiR-19b Acts as a Diagnostic Marker for Pancreatic Cancer - Wang, Lei; Wu, Jinxiang; Ye, Naikuan; Li, Feng; Zhan, Hanxiang; Chen, Shihong; Xu, Jianwei (Frontiers in Oncology, 2021)
Background: Diagnosis of pancreatic cancer (Pca) is challenging. This study investigated the value of plasma-derived exosome miR-19b (Exo-miR-19b) in diagnosing patients with Pca. Methods: Plasma was collected from 62 patients with Pca, 30 patients with other pancreatic tumor (OPT), 23 patients with chronic pancreatitis (CP), and 53 healthy volunteers. MiR-19b levels in plasma-derived exosomes were detected. Results: Plasma-derived Exo-miR-19b levels normalized using miR-1228 were significantly lower in Pca patients than in patients with OPT, CP patients and healthy volunteers. The diagnostic values of Exo-miR-19b normalized using miR-1228 were superior to serum CA19-9 in differentiating Pca patients from healthy volunteers (AUC: 0.942 vs. 0.813, P=0.0054), potentially better than CA19-9 in differentiating Pca patients from CP patients (AUC: 0.898 vs. 0.792, P=0.0720), and equivalent to CA19-9 in differentiating Pca patients and patients with OPT (AUC: 0.810 vs. 0.793, P=0.8206). When normalized using cel-miR-39, Exo-miR-19b levels in Pca patients were significantly higher than those in patients with OPT, CP patients and healthy volunteers. The diagnostic values of Exo-miR-19b normalized using cel-miR-39 were equivalent to CA19-9 in differentiating Pca patients from healthy volunteers (AUC: 0.781 vs. 0.813, P=0.6118) and CP patients (AUC: 0.672 vs. 0.792, P=0.1235), while it was inferior to CA19-9 in differentiating Pca patients from patients with OPT (AUC: 0.631 vs. 0.793, P=0.0353). Conclusion: Plasma-derived Exo-miR-19b is a promising diagnostic marker for Pca. The diagnostic value of plasma-derived Exo-miR-19b normalized using miR-1228 is superior to serum CA19-9 in differentiating patients with Pca from healthy volunteers.